(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
Social media, as Shearer (2019) posits, has become an increasingly popular component of our everyday life, as it provides a platform where people across the world can communicate through exchange of messages, sharing of knowledge, and interaction with each other, regardless of the distance that separates them. Such interconnectedness and interdependence of social media users, has become a pattern and a routine due to the ease of communication, and the accessibility of plenty of information available from various social media platforms such as Facebook, Instagram, WeChat and YouTube.